2021
DOI: 10.5539/ass.v18n1p23
|View full text |Cite
|
Sign up to set email alerts
|

Internal and External Factors Influencing Millennials’ Sharing Behaviour of Online Video Advertisements

Abstract: This study aimed to uncover the internal and external factors driving Millennial consumers to engage in Online Video Advertisements (OVAs) sharing. Underpinned by the Theory of Planned Behaviour (TPB), the internal factors tested in this study were attitude, subjective norms, and perceived behavioural control. The external factors predicted to influence consumers’ intention and actual sharing behaviour of OVAs were company reputation, brand awareness, and celebrity endorsement were underpinned by Sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Cheung and Lee (2010) found that social norms and social identity have a certain impact on users who use online social networks, such as Facebook. Zainordin et al (2021) studied the advertising sharing behaviors of young consumers and found that perceived social norms have an impact on sharing intentions. In fact, past studies have consistently stated that social norms have a direct effect on intention and actual behavior.…”
Section: Social Norms and News Sharingmentioning
confidence: 99%
“…Cheung and Lee (2010) found that social norms and social identity have a certain impact on users who use online social networks, such as Facebook. Zainordin et al (2021) studied the advertising sharing behaviors of young consumers and found that perceived social norms have an impact on sharing intentions. In fact, past studies have consistently stated that social norms have a direct effect on intention and actual behavior.…”
Section: Social Norms and News Sharingmentioning
confidence: 99%